Presentism: Foreigner-Friendly or Xenophobic?. Issue 3 (2nd July 2016) - Frances, Bryan
Abstract : I argue that, for all we know, there are perfectly ordinary actual entities that are temporal in the usual sense and yet never present, past, or future. This epistemic fact requires us to modify the theses of presentism and eternalism. More importantly, it generates three new and quite serious objections to presentism, which I formulate and partially evaluate in this paper.